Characterization of Gut Microbiota and Exploration of Potential Predictive Model for Hepatocellular Carcinoma Microvascular Invasion - Zhang, Ningning; Wang, Zeyu; Lv, Jiayu; Zhang, Shuwen; Liu, Yang; Liu, Tian; Li, Wang; Gong, Lan; Zhang, Xiaodong; El-Omar, Emad M.; Lu, Wei (Frontiers in Medicine, 2022)
Background: The association between gut microbiota and microvascular invasion (MVI) in hepatocellular carcinoma (HCC) patients remains unclarified. Hence the microbiome analysis of HCC patients might predict MVI development as an accurate, non-invasive and convenient assessment. The aim of this study was to investigate the characteristics of gut microbiota in HCC-MVI patients and establish a microbial prediction model of HCC-MVI based on microbiome study. Methods: Fecal samples were collected from 59 HCC patients (24 of the total with MVI disease) and 16 healthy controls, and further analyzed by 16S rRNA amplicon sequencing. Bioinformatics methods were used to analyze the obtained sequence data. The diagnostic performance of microbiome characteristics in predicting MVI was assessed by receiver operating characteristic (ROC) curves. The correlation between gut microbiota and tumor microenvironment (TME) in HCC-MVI group were further analyzed with Immunohistochemistry and immunofluorescence assay. Results: A significant differentiation trend of microbiota composition and structure was observed between the HCC-MVI group and those without vascular invasion (HCC-NVI). Compared with HCC-NVI group and healthy controls，Klebsiella, Proteobacteria, Prevotellaceae and Enterobacteriaceae were significantly enriched, whereas Firmicutes, Ruminococcus and Monoglobaceae were significantly decreased in HCC-MVI fecal samples. Klebsiella was considered to be the key microbiome signature for HCC-MVI patients. The area under the curve (AUC) of the established HCC-MVI microbial prediction model was 94.81% (95% CI: 87.63%-100%). The percentage of M2 type tumor-associated macrophage (TAMs) was increased in HCC-MVI group compared with HCC-NVI group (P < 0.001). M2-type TAMs in TME was negatively correlated with Shannon and Simpson index of HCC-MVI gut microbiota (all P < 0.01). In addition, predicted KEGG pathways showed that the functional differences in metabolic pathways of microbiome varied with groups. Conclusions: The results indicated that differences existed in the fecal microbiome of HCC-MVI patients and healthy controls, the prediction model of HCC-MVI established with certain gut bacteria signature may have potential to predict HCC-MVI and the characteristics of fecal microbiome in HCC patients may associate with TME, though future larger-sample studies are required to validate this supposition.